A Combined Heat and Power System for Solid-fuel Stoves Using Thermoelectric Generators. (August 2015) - Montecucco, Andrea; Siviter, Jonathan; Knox, Andrew R.
Abstract: Solid-fuel stoves are used in developing countries, remote locations, and in general more commonly due to convenient fuel cost. The possibility of using the stove heat to heat water and produce electricity represents an added benefit. This work presents an application of thermoelectric generators to a solid-fuel stove to concurrently charge a lead-acid battery and transfer heat to water for heating or household use. The feasibility of the proposed CHP system is demonstrated for a common solid-fuel stove. This system produces an average of 600 Wth and 27 Wel during a 2-h long experiment, in which the TEG efficiency is around 5% and the MPPT efficiency of the power converters used is demonstrated.